2019
DOI: 10.33221/jiki.v8i01.434
|View full text |Cite
|
Sign up to set email alerts
|

Beberapa Faktor yang Berpengaruh terhadap Pencegahan Puerperium Infections

Abstract: Infeksi nifas bisa berasal dari luka pada jalan  lahir  yang  merupakan  media  yang  baik  untuk  berkembangnya kuman. Penanganan komplikasiyang lambat dapat menyebabkan terjadinya kematian ibu post partum. Tujuan penelitian ini adalah mengetahui pengaruh langsung dan tidak langsung serta besarannya sumber informasi, peran nakes, peran kader, peran keluarga dan personal hygiene perception terhadap pencegahan puerperium infections pada ibu nifas di UPTD Puskesmas Kecamatan Pontianak Selatan Kalimantan Barat ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Table 1 Regarding Sleep Quality, a study by (Kim, Kim, & Lim, 2021) found that both shorter and longer sleep durations, as well as longer working hours, are associated with a higher risk of suicidal ideation. A study by (Suciati & Wulandari, 2022) stated that workers with poor sleep quality are influenced by short sleep duration, sleep disturbances, and difficulties concentrating during work.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 Regarding Sleep Quality, a study by (Kim, Kim, & Lim, 2021) found that both shorter and longer sleep durations, as well as longer working hours, are associated with a higher risk of suicidal ideation. A study by (Suciati & Wulandari, 2022) stated that workers with poor sleep quality are influenced by short sleep duration, sleep disturbances, and difficulties concentrating during work.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of inventory used in this study is a measuring instrument developed by research conducted by (Suciati & Wulandari, 2022) which is formulated as follows: (Suciati & Wulandari, 2022) "Inventory Intensity" = "Total Inventory" Total Inventory X 100%…”
Section: Inventory Intensitymentioning
confidence: 99%